One-dimensional nanostructured materials for energy storage applications - Sun, Leimeng (2017)
This thesis covers the applications of one dimensional nanostructured materials in energy storage devices such as lithium-ion batteries (LIBs) and micro-supercapacitors (MSCs). Besides energy storage devices fabrication, integration of energy storage devices with microelectronic devices is also included. The chapter 1 introduces the background, motivations, objectives and major contributions of this thesis. Chapter 2 presents two important one-dimensional (1D) nanostructured materials, vertical-aligned carbon nanotubes (VACNTs) array and silicon nanowires (SiNWs) array, produced with our own techniques. The corresponding experimental details and morphology characterizations are given in this chapter as well. In chapter 3, fabrication processes and electrochemical performances of two novel LIBs anodes basing on 1D nanostructured materials are introduced. The great contribution of 1D nanomaterial in improving the LIBs performance has been proved. Chapter 4 describes two superior planar micro-supercapacitors manufactured through using 1D nanostructured materials. In which, the unique 1D nanostructures greatly strengthen the current delivery capability and stability of MSCs, even on the soft substrate. Development of an integrated supercapacitor with a photodetector on the same 1D nanostructured materials based substrate is shown in chapter 5. It demonstrates that two components are able to function well in a microelectronic system for a high portability. Finally, chapter 6 provides the conclusive remarks and recommendation for future work of 1D nanostructured materials applied for energy storage devices.